Age Determination in Manipuri Subjects from the Eruption of Teeth and Epiphyseal Union of Upper Limb - Ragui, Soreingam; Singh, Th Bijoy; Meera, Th; Nabachandra , H (Journal of Indian Academy of Forensic Medicine, 2015)
The present study aims to determine the age of the Manipuri population by computing regression  formulae from the eruption of the permanent canine & second molar, and also from the epiphyseal union  at the elbow and wrist joints. 320 Manipuri subjects of 10 to 15 years (i.e. 244 male, 76 female) coming to  the Forensic Medicine department of a tertiary health care hospital at Imphal for age determination from  October 2011 to September 2013 were studied. The age of eruption of permanent canines is 10 years in  both sexes; whereas the eruption of second permanent molar is 11-12 years in females and 11-14 years  in males in the Manipuri population. The medial epicondyle fuses with the shaft of humerus in 11-14 years  in both the sexes. The epiphyseal fusions of 1st metacarpal take place in 13 -15 years in females and 12- 14 years in males. A combined regression formula was calculated for males and females. It can be used  as a standard for determination of age in Manipuri subjects by substituting the various stages of dental  eruption or epiphyseal union.
Keywords: Canine; Second Molar; Epiphyseal Union; Regression Formulae